Military Leadership of Khalid bin Walid in the Battle of Mu’tah - Rospiadi, Muhammad Luthfi Ader; Barok, Arif Misfahul; Attaqy, Muhammad Syafiq (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The Battle of Mu’tah was one of the most significant battles in Islamic history, taking place in 629 CE between the Muslim army and the Byzantine Empire. One of the central figures in this event was Khalid bin Walid, renowned as an exceptional military commander in Islamic history. This study aims to examine Khalid bin Walid’s leadership during the Battle of Mu’tah, particularly his strategies, tactics, and decisiveness after assuming command following the deaths of the previous commanders on the battlefield. The research uses a library research method with a descriptive qualitative approach. Findings reveal that Khalid bin Walid successfully led the Muslim army in a strategic withdrawal from an uneven battle, avoiding total defeat and saving many lives. His leadership was marked by resilience, military intelligence, and courage, which earned him the title "The Sword of Allah." This study emphasizes the importance of adaptive leadership in critical situations and Khalid bin Walid’s contribution to sustaining the early Islamic struggle. The Battle of Mu’tah, a key historical event in the development of Islamic da’wah, occurred in 629 CE (8 AH), involving the Muslim army against the Byzantine forces and their allies near Mu’tah, close to the Levantine border. In this battle, three primary Muslim commanders — Zaid bin Harithah, Ja’far bin Abi Talib, and Abdullah bin Rawahah — were martyred in succession. Amid this crisis, Khalid bin Walid stepped up to take command and led the Muslim forces, who were vastly outnumbered. This research aims to examine the form and characteristics of Khalid bin Walid’s leadership in the context of the Battle of Mu’tah, especially in dealing with battlefield pressure and emergency conditions. The study concludes that Khalid bin Walid employed a flexible, intelligent, and calculated military strategy, including tactical maneuvers that successfully misled the enemy and allowed the Muslim forces to retreat in an orderly manner without total defeat. His success demonstrated an adaptive, courageous, and wise leadership capacity, prompting the Prophet Muhammad (peace be upon him) to grant him the title "Saifullah" (The Sword of Allah). This research concludes that effective leadership in critical situations is crucial to the continuity of a struggle and provides important lessons in crisis management and early Islamic military strategy.